2005
DOI: 10.1080/15287390590895847
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Metabolic Interaction between Trihalomethanes and Chloroacetic Acids using Rat Liver Microsomes

Abstract: The aim of this study was to investigate the in vitro metabolism of trihalomethanes (THMs) in the presence of trichloroacetic acid (TCA), dichloracetic acid (DCA), monochloroacetic acid (MCA), and 4-methylpyrazole (4-MP) using liver microsomes from male Sprague-Dawley rats. Using the vial equilibration technique, initial experiments were carried out with starting concentrations of approximately 40 ppm THMs and 12-22 mM chloroacetic acids. The results indicated a mutual metabolic inhibition between THMs present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Trihalomethanes (THMs) and haloacetic acids (HAAs) are the two most prevalent classes of DBPs found in chlorinated drinking water worldwide including in China. , Human exposure to DBPs occurs through water-use activities such as chlorinated water consumption, showering/bathing, and swimming . After exposure, DBPs such as brominated THMs and HAAs are metabolized into mutagenic intermediates through a conjugation with glutathione, resulting in potentially adverse health effects. Epidemiological studies have suggested that exposure to DBPs is associated with elevated risk of cancer , and adverse male reproductive effects. Prenatal exposure to DBPs has also been reported to be associated with a variety of adverse birth outcomes such as preterm delivery, small for gestational age, low birth weight, and fetal growth restriction. However, the findings remain inconclusive and inconsistent. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trihalomethanes (THMs) and haloacetic acids (HAAs) are the two most prevalent classes of DBPs found in chlorinated drinking water worldwide including in China. , Human exposure to DBPs occurs through water-use activities such as chlorinated water consumption, showering/bathing, and swimming . After exposure, DBPs such as brominated THMs and HAAs are metabolized into mutagenic intermediates through a conjugation with glutathione, resulting in potentially adverse health effects. Epidemiological studies have suggested that exposure to DBPs is associated with elevated risk of cancer , and adverse male reproductive effects. Prenatal exposure to DBPs has also been reported to be associated with a variety of adverse birth outcomes such as preterm delivery, small for gestational age, low birth weight, and fetal growth restriction. However, the findings remain inconclusive and inconsistent. , …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Human exposure to DBPs occurs through water-use activities such as chlorinated water consumption, showering/bathing, and swimming. 3 After exposure, DBPs such as brominated THMs and HAAs are metabolized into mutagenic intermediates through a conjugation with glutathione, 4 resulting in potentially adverse health effects. Epidemiological studies have suggested that exposure to DBPs is associated with elevated risk of cancer 5,6 and adverse male reproductive effects.…”
Section: ■ Introductionmentioning
confidence: 99%